Kepemimpinan Pemuda Kristen di Era Digital: Pelayanan dalam Transformasi Teknologi untuk Membangun Komunitas Iman yang Relevan - Aritonang, Nineson setiawan; Manurung, Kosma (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2024)
Leadership in the church for Christian youth leadership in this digital era, demands the role of human resources who have dynamic adaptation to change for the sake of significant changes in technology, because it is to build a relevant community of spirituality and faith. Where technological transformation has changed the landscape of church communication and ministry, it requires new strategies that combine Christian values with technological innovation.  This is the purpose of the paper, so that youth leadership can see opportunities and utilize technology in church ministry to create and build relevant spirituality and faith today. Using a descriptive qualitative method with a literature study approach, it can be concluded that the important role of Christian youth leadership in the digital era, as an effort in service to transform technology to build relevant spirituality and faith. That is, youth leadership needs to understand the nature of Christian leadership and the use of technology in church services that aim to develop spiritual leadership in the digital era, it can build relevant spiritual and faith communities. So the important role of everything lies in youth leadership in the digital era, so that Christian youth can become agents of change in forming spiritual and faith communities that have a positive impact in the digital era.AbstrakKepemimpinan dalam gereja bagi kepemimpinan pemuda Kristen di era digital ini, menuntut peran sumber daya manusia yang memiliki adaptasi yang dinamis terhadap perubahan demi perubahan yang signifikan dalam teknologi, sebab hal itu untuk membangun komunitas spritulitas dan iman yang relevan. DI mana transformasi teknologi telah mengubah lanskap komunikasi dan pelayanan gereja, memerlukan strategi baru yang menggabungkan nilai-nilai kekristenan dengan inovasi teknologi.  Ini tang menjadi tujuan dari tulisan, sehingga kepemimpinan Pemuda dapat melihat peluang dan memanfaatkan teknologi dalam pelayanan gereja untuk menciptakan  dan membangun spritualitas dan iman yang relevan saat ini. Menggunakan metode kualitatif deskritif dengan pendekatan studi literature maka dapat disimpulkan bahwa peran penting dari kepemimpinan pemuda kristen di era digital, sebagai upaya dalam pelayanan untuk mentransformasi teknologi membangun spritualitas dan  iman yang relevan. Yaitu kepemimpinan pemuda perlu memahami hakikat kepemimpinan Kristen dan Penggunaan Teknologi dalam Pelayanan Gereja yang bertujuan untuk Mengembangkan Kepemimpinan Rohani di Era Digital, hal itu dapat membangun komunitas Spritual dan Iman yang relevan. Maka peran penting semuanya itu terletak padaa kepemimpinan pemuda di era digital, supaya pemuda Kristen dapat menjadi agen perubahan dalam membentuk komunitas spiritual dan iman yang berdampak positif dalam era digital.